Pevonedistat, a Nedd8-activating enzyme inhibitor, in combination with ibrutinib in patients with relapsed/refractory B-cell non-Hodgkin lymphoma - Pallawi Torka; Swetha Kambhampati Thiruvengadam; Lu Chen; Xiaoguang Wang; Canping Chen; Dan Vuong; Hanjun Qin; Alexandra Muir; Kirsten Orand; Ivana Borja; D. Lynne Smith; Alex F. Herrera; et al. (Blood Cancer Journal, 2023)
Abstract Pevonedistat (TAK924) is a Nedd8-activating enzyme inhibitor with preclinical activity in non-Hodgkin lymphoma (NHL). This open-label, Phase I, multicenter, investigator-sponsored study enrolled patients with relapsed/refractory (R/R) NHL and chronic lymphocytic leukemia (CLL). The primary objective was safety. Pevonedistat was given intravenously on days 1, 3, 5 of a 21-day cycle for 8 cycles at five dose levels (15 to 50 mg/m2); ibrutinib was administered at 420 or 560 mg orally daily continuously. Eighteen patients with NHL were enrolled, including 8 patients with mantle cell lymphoma (MCL) and 4 patients with CLL. One dose-limiting toxicity (mediastinal hemorrhage) occurred at 50 mg/m2 of pevonedistat which is the estimated maximum tolerated dose. Bruising and diarrhea were the most common adverse events (56% and 44%). Atrial fibrillation occurred in 3 patients (17%). Grade ≥3 toxicities included arthralgia, atrial fibrillation, bone pain, diarrhea, hypertension, and mediastinal hemorrhage (one patient each). The overall response rate (ORR) was 65% (100% ORR in MCL). Pevonedistat disposition was not modified by ibrutinib. scRNA-Seq analysis showed that pevonedistat downregulated NFκB signaling in malignant B-cells in vivo. Thus, pevonedistat combined with ibrutinib demonstrated safety and promising early efficacy in NHL and CLL. NAE inhibition downregulated NFκB signaling in vivo.